Criminal Procedure Aspects of the International Cooperation of States in the Field of Combating Transnational Organized Crime - SEILKHANOVA, Saida; SHEGEBAYEVA, Aigerim; OTARBAYEVA, Azina; ABILEZOV, Yestay (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).27, 2019)
The research dwells on criminal and legal aspects of international cooperation in the field of combating transnational organized crime. The issues of fighting against transnational organized crime affect all states without exception.Therefore the formation of national legislation in this area should consider the international experience in combating this phenomenon and utilize international legal acts that serve as the basis for creating not only specific norms but also a national policy to counteract transnational organized crime. This article aims at studying different forms of interaction between agencies carrying out criminal procedure activities on an international scale and developing recommendations in order to introduce the most effective methods of such interaction into the procedural practice and legislation of the Republic of Kazakhstan. The authors of the article analyze the international legal framework, regulatory documents and law enforcement practice of a number of states (mainly the US, the EU, etc.). The authors conclude that criminal procedure aspects of the international legal framework for countering transnational organized crime in the context of the legislation of Kazakhstan require further development, improvement and comprehensive research. The study results obtained by the authors can serve as the basis for further scientific discussions and new surveys, as well as be used in the development of educational and practical manuals on the study of international cooperation both in criminal proceedings and in the fight against transnational organized crime.